Superoxide Dismutases in Polymorphonuclear Leukocytes - Salin, Marvin L. (1974)
Isolated human polymorphonuclear leukocytes were found to contain two distinct superoxide dismutases, electrophoretically identical to the superoxide dismutases found in other human tissues. One is inhibited by cyanide and is located in the cytosol. The other is not inhibited by cyanide and is mitochondrial. These findings disagree with reports by other laboratories, which did not find the cyanide-sensitive cytoplasmic enzyme. The superoxide dismutase-containing preparation of leukocytes released large amounts of superoxide into the medium when the cells were phagocytizing, suggesting that, if the cell population is homogeneous, superoxide production probably takes place on the outer surface of the cell membrane, in addition to inside the phagocytic vacuole.